Yield and quality of ‘Italia’ grapes submitted to irrigation and fertilization control at the San Francisco Valley, Brazil - Pimenta Martins Andrade, Victor Pimenta; Silva Dias, Merideise Silva; Aliçandro Bezerra da Silva, José Bezerra; Sebastião Costa de Sousa, José Costa; Lima Simões, Welson Lima (Comunicata Scientiae, 2016)
The aim of this research was to evaluate aspects related to flowering, fruiting and quality of ‘Italia’ grape produced under different irrigation and fertilization. The experiment was performed from October, 2014 to February, 2015, in a production area of 0.50 ha at IFSERTÃO-PE, in Petrolina-PE, Brazil. The experiment was carried out in a randomized blocks design, with a split block scheme, with four irrigation treatments (plots), four fertilizer treatments (subplots) and four repetitions. The plots consisted of the multiplying factors, 0.75 (L1); 1.00 (L2); 1.25 (L3) and 1.50 (L4), of the recommended crop coefficients (Kc) by Embrapa Semi-Arid for the ‘Italia’ grapevine. The subplots were composed by the factors 1.00 (AD1), 0.75 (AD2), 0.50 (AD3) and 0.25 (AD4) of the recommended fertilization with an BIOSON as organic product (commercial name). It was observed that the reduction in water depth provided greater number of buds per branch and a larger number of clusters per plant. The highest yields were obtained with lower irrigation depths and 50% and 65% of the recommended fertilization. The highest soluble solids of the fruit were achieved using the 75% of irrigation Kc and 25% of recommended mineral fertilization. The lower total acidity values were obtained with the Kc multiplication factors that were lower than 1.04 and higher than 1.22.